Prophetic Transformative Pedagogy in Monotheistic Education: A Thematic Qur'anic Analysis of Prophet Ibrahim's Dialogue in Q.S. Al-Anbiya' (21:51–70) - Nurul Hidayat (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
Contemporary Islamic education requires pedagogical approaches that integrate intellectual development, spiritual formation, ethical responsibility, and social engagement in response to increasingly complex educational challenges. Although the educational narrative of Prophet Ibrahim has been widely examined from theological and exegetical perspectives, its relevance to transformative pedagogy has received limited scholarly attention. This study aims to analyze the educational dialogue of Prophet Ibrahim in Q.S. Al-Anbiya' (21:51–70) through the lens of transformative pedagogy and to develop a conceptual framework for contemporary Islamic education. A qualitative library research design was employed using a thematic Qur'anic interpretation (tafsir maudhu'i) approach. The analysis was based on the selected Qur'anic verses, classical and contemporary tafsir, and transformative pedagogical theory through documentation, thematic coding, interpretative analysis, and conceptual synthesis. The findings reveal that Prophet Ibrahim employed dialogical, reflective, and evidence-based educational strategies that encouraged critical questioning, rational argumentation, cultural deconstruction, moral resilience, and transformative leadership. The educational process described in the Qur'an operates through four interconnected dimensions, namely cognitive, moral, spiritual, and social transformation, all of which originate from divine guidance (rusyd) as the epistemological foundation of prophetic education. Based on these findings, this study proposes the Integrated Prophetic Transformative Pedagogy (IPTP) Model, which conceptualizes prophetic education as a holistic process integrating revelation, critical inquiry, ethical character, faith formation, and community transformation. The proposed framework contributes to bridging Qur'anic educational studies with contemporary transformative pedagogy while offering a theoretical foundation for curriculum development, character education, leadership education, and Islamic educational reform in contemporary contexts.